Elevated liver enzymes and cardiovascular mortality: a systematic review and dose–response meta-analysis of more than one million participants. Issue 5 (May 2019) - Rahmani, Jamal; Miri, Ali; Namjoo, Iman; Zamaninour, Negar; Maljaei, Mohammad B.; Zhou, Kehua; Cerneviciute, Raminta; Mousavi, Seyed M.; Varkaneh, Hamed K.; Salehisahlabadi, Ammar; Zhang, Yong
Abstract : Gamma glutamyl transferase (GGT), alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) are commonly used liver function markers. We performed a dose–response meta-analysis to investigate the association between liver enzymes and cardiovascular disease (CVD) mortality in prospective cohort studies. We conducted a systematic search up to April 2018 in Medline/PubMed, Scopus, Cochrane, and Embase databases. Combined hazard ratios (HRs) with 95% confidence intervals (CIs) were estimated using a random-effects model as described by DerSimonian and Laird. Dose–response analysis was also carried out. Twenty-three studies with 1 067 922 participants reported association between GGT and CVD mortality and were included in our analysis. Pooled results showed a significant association between GGT and risk of CVD mortality (HR: 1.62; 95% CI: 1.47–1.78, P =0.001, P -heterogeneity=0.001) and it was HR: 0.87; 95% CI: 0.73–1.07; P =0.221, P -heterogeneity=0.028, for ALT. There was a direct association between baseline levels of ALP and AST/ALT ratio with CVD mortality (HR: 1.45; 95% CI: 1.11–1.89; P =0.005, P -heterogeneity=0.026, and HR: 2.20; 95% CI: 1.60–3.04; P =0.001, P -heterogeneity=0.540, respectively). Pooled results did not show any significant association between AST and the risk of CVD mortality (HR: 1.20; 95% CI: 0.83–1.73; P =0.313, P -heterogeneity=0.024). Moreover, there was a significant nonlinear association between GGT and ALP levels and the risk of CVD mortality ( P =0.008 and 0.016, respectively). Our dose–response meta-analysis revealed a direct relationship between GGT and ALP levels and the risk of CVD mortality. High levels of GGT, ALP and AST/ALT were associated with an increased CVD mortality rate. Abstract : Supplemental Digital Content is available in the text.